2015
DOI: 10.1063/1.4927406
|View full text |Cite
|
Sign up to set email alerts
|

Transparency of graphene for low-energy electrons measured in a vacuum-triode setup

Abstract: Graphene, being an atomically thin conducting sheet, is a candidate material for gate electrodes in vacuum electronic devices, as it may be traversed by low-energy electrons. The transparency of graphene to electrons with energies between 2 and 40 eV has been measured by using an optimized vacuum-triode setup. The measured graphene transparency equals ∼60% in most of this energy range. Based on these results, nano-patterned sheets of graphene or of related two-dimensional materials are proposed as gate electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…The thermal robustness of graphene has been demonstrated in Ref. 15 where the transparency of low energy electrons was measured in a triode setup similar to the one discussed here.…”
Section: Graphene As a Gate Electrodementioning
confidence: 97%
See 2 more Smart Citations
“…The thermal robustness of graphene has been demonstrated in Ref. 15 where the transparency of low energy electrons was measured in a triode setup similar to the one discussed here.…”
Section: Graphene As a Gate Electrodementioning
confidence: 97%
“…The measured data of the graphene transparency in a triode setup given in Ref. 15 include these losses and they are therefore taken into account in our efficiency considerations below.…”
Section: B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, electrons injected in the body of nanotubes (or in the interstices) by DM-electron scatterings, might go through the walls, with definite transmission coefficients, and undergo multi-scattering events, crossing several nanotubes, before exiting from the array. As a benchmark for our analysis, we have used the results of some experimental studies on the determination of transmission coefficients of electrons through graphene planes [12][13][14][15][16]. More information from experiments of this kind would be extremely useful for determining directly also reflection and absorption coefficients.…”
mentioning
confidence: 99%
“…Indeed in the experiments reported in [12][13][14][15][16] it is found that the largest part of the electron beam impinging orthogonally to the graphene monolayer (deposited on a surface with holes) is transmitted or reflected.…”
mentioning
confidence: 99%